2020
DOI: 10.3389/fphys.2020.00458
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Lymph Flow, and Lipid and Drug Transport Scale Allometrically From Pre-clinical Species to Humans

Abstract: Trevaskis et al. Allometry of Drug in Lymph following absorption. Overall, this study proposes that intestinal lymphatic flow, and lymphatic lipid and drug transport in humans is most similar to species with higher body mass such as dogs and underestimated by studies in rodents. Notably, lymph flow and lipid transport in humans can be predicted from animal data via allometric scaling suggesting the potential for similar relationships with drug transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…With respect specifically to flymph, this is influenced primarily by a drug's ability to associate with chylomicrons in the enterocyte, which in turn is dependent on the drug's physicochemical properties, availability of a source of lipids (especially long-chain lipids) and characteristics of the formulation [25,32]. By stimulating the production of lymph, dietary or formulation-based lipids can also increase mesenteric lymphatic flow [41],…”
Section: The Interplay Between Cbd Oral Absorption Lymphatic Transport and Liver Firstpass Metabolismmentioning
confidence: 99%
“…With respect specifically to flymph, this is influenced primarily by a drug's ability to associate with chylomicrons in the enterocyte, which in turn is dependent on the drug's physicochemical properties, availability of a source of lipids (especially long-chain lipids) and characteristics of the formulation [25,32]. By stimulating the production of lymph, dietary or formulation-based lipids can also increase mesenteric lymphatic flow [41],…”
Section: The Interplay Between Cbd Oral Absorption Lymphatic Transport and Liver Firstpass Metabolismmentioning
confidence: 99%
“…lymph flow rate increases in direct proportion to increases in body mass to the power of 0.9 (Trevaskis et al, 2020). Using the same calculations for allometric analysis (Trevaskis et al, 2020), the scaling exponent for cervical lymph flow rate from one side was 0.8 across species (rats, rabbits, cats and sheep). This suggests cervical lymph flow rate also increases in proportion to body weight across species and that studies conducted in several species may be able to predict cervical lymph flow rate and transport in larger species, including humans.…”
Section: Cervical Lymph Flow Rate Is Allometrically Scaled Across Rat...mentioning
confidence: 87%
“…In previously conducted studies by our laboratory, mesenteric and thoracic lymph flow rates were shown to scale allometrically across species (mouse, rat, dog and human) with an exponent of ~0.9, i.e. lymph flow rate increases in direct proportion to increases in body mass to the power of 0.9 (Trevaskis et al, 2020). Using the same calculations for allometric analysis (Trevaskis et al, 2020), the scaling exponent for cervical lymph flow rate from one side was 0.8 across species (rats, rabbits, cats and sheep).…”
Section: Cervical Lymph Flow Rate Is Allometrically Scaled Across Rat...mentioning
confidence: 94%
“…Both absolute and relative bioavailability via lymph increase with increasing bodyweight of animal species tested (dog > rat > mouse; Trevaskis et al, 2013). Using recently published allometric scaling formulas (Trevaskis et al, 2020), abiraterone F AL in humans could be expected approximately fourfold higher than in rats, meaning 0.60% for the capsule formulation. Given the low absolute bioavailability, this could result in F RL of 10–15% in men.…”
Section: Discussionmentioning
confidence: 99%